Case Report: Malignant Melanoma Associated With COVID-19: A Coincidence or a Clue? - Leis, A. Arturo; Montesi, Anna Peyton; Khan, Sariya Maryam; Montesi, Michael (Frontiers in Medicine, 2022)
Following SARS-CoV-2 infection in humans, there is upregulation of proinflammatory molecules S100 calcium binding protein B (S100B), high-mobility group box-1 (HMGB1), osteopontin (OPN), tumor necrosis factor alpha (TNF-α) and other cytokines that promote hyperinflammation. The same immunoregulatory proteins that fuel the COVID-19 ‘cytokine storm’ are also produced by melanoma cells and various other cancers to promote tumorigenesis. We report three cases of malignant melanoma associated with severe COVID-19, the first two with amelanotic melanoma and the third with hypopigmented melanoma. It is noteworthy that we did not search for these cases. Patient 1 is a personal acquaintance and cases 2 and 3 were hospitalized and worked at our rehabilitation center, respectively. We hypothesize that SARS-CoV-2 induced inflammatory tumorigenic proteins in the microenvironment that may have contributed to the de novo development (case 1), aggressive growth (case 2), or recurrence (case 3) of these malignant tumors. Moreover, high concentrations of the same proinflammatory proteins found in the ‘cytokine storm’ associated with COVID-19, including TNF-α, interleukin (IL)-1α, IL-1β, IL-6, and ferritin, also induce skin depigmentation or hypopigmentation by interfering with tyrosinase synthesis, the enzyme that catalyzes the rate-limiting step of pigmentation. Hence, the marked elevation of the biological effectors that decrease skin pigmentation may also reduce pigmentation in malignant melanomas, resulting in amelanotic or hypopigmented lesions. Although it is certainly possible that the occurrence of melanoma following COVID-19 is coincidental, the ability of SARS-CoV-2 to increase expression of proinflammatory and tumorigenic molecules warrants further investigations to determine if there is an association between these disease processes or implications for patients with melanoma or other cancers who develop COVID-19.